Interactive Effects of Genotype and Molybdenum Supply on Yield and Overall Fruit Quality of Tomato - Sabatino, Leo; D'Anna, Fabio; Iapichino, Giovanni; Moncada, Alessandra; D'Anna, Eleonora; De Pasquale, Claudio (Frontiers in Plant Science, 2019)
Molybdenum (Mo) is an essential trace element for plant growth, development, and production. However, there is little known about the function and effects of molybdenum in tomato plants. The present study assessed the influences of different Mo concentrations on four tomato F1 hybrids (“Bybal” F1, “Tyty” F1, “Paride” F1, and “Ornela” F1) grown using a soilless system with different Mo levels [0.0, 0.5 (standard NS), 2.0, and 4.0 μmol L−1, respectively]. The crop yield, plant vigor, fruit skin color, TA, fruit water content as well as the accumulation of SSC, and some antioxidant compounds such as lycopene, polyphenols and ascorbic acid were evaluated. The minerals concentration, including nitrogen (N), Mo, iron (Fe), and copper (Cu), were measured in tomato fruits. Results revealed that tomato plants grown with 2.0 μmol Mo L−1 compared to plants grown with 0.5 μmol Mo L−1 incurred a significant increase of total yield by 21.7%, marketable yield by 9.1%, aboveground biomass by 16.7%, plant height at 50 DAT by 6.5%, polyphenol content by 3.5%, ascorbic acid by 1.0%, SSC by 3.5%, N fruit content by 24.8%, Mo fruit content by 20.0%, and Fe fruit content by 60.5%. However, the Mo concentration did not significantly influence the average fruit weight, b* fruit skin color coordinate and TA. Furthermore, tomato fruits from plants grown with 2.0 μmol Mo L−1 showed a lower Cu fruit content (16.1%) than fruits from plants grown with 0.5 μmol Mo L−1 (standard NS). Consequently, our study highlights the different behavior of the tomato genotypes tested when subjected to different levels of Mo concentration in the nutrient solution. Nevertheless, taking all in consideration our results clearly suggest that a Mo fertilization of 2.0 μmol Mo L−1 effectively enhance crop performance and overall fruit quality of tomato.